Frontier molecular orbitals of a single molecule adsorbed on thin insulating films supported by a metal substrate: electron and hole attachment energies. (1st August 2017) - Scivetti, Iván; Persson, Mats
Abstract: We present calculations of vertical electron and hole attachment energies to the frontier orbitals of a pentacene molecule absorbed on multi-layer sodium chloride films supported by a copper substrate using a simplified density functional theory (DFT) method. The adsorbate and the film are treated fully within DFT, whereas the metal is treated implicitly by a perfect conductor model. We find that the computed energy gap between the highest and lowest unoccupied molecular orbitals—HOMO and LUMO -from the vertical attachment energies increases with the thickness of the insulating film, in agreement with experiments. This increase of the gap can be rationalised in a simple dielectric model with parameters determined from DFT calculations and is found to be dominated by the image interaction with the metal. We find, however, that this simplified model overestimates the downward shift of the energy gap in the limit of an infinitely thick film.